Safety and efficacy of abexinostat, a pan-histone deacetylase inhibitor, in non-Hodgkin lymphoma and chronic lymphocytic leukemia: results of a phase II study - Ribrag, Vincent (Haematologica, 2017)
Histone deacetylase inhibitors are members of a class of epigenetic drugs that have proven activity in T-cell malignancies, but little is known about their efficacy in B-cell lymphomas. Abexinostat is an orally available hydroxamate-containing histone deacetylase inhibitor that differs from approved inhibitors; its unique pharmacokinetic profile and oral dosing schedule, twice daily four hours apart, allows for continuous exposure at concentrations required to efficiently kill tumor cells. In this phase II study, patients with relapsed/refractory non-Hodgkin lymphoma or chronic lymphocytic leukemia received oral abexinostat at 80 mg BID for 14 days of a 21-day cycle and continued until progressive disease or unacceptable toxicity. A total of 100 patients with B-cell malignancies and T-cell lymphomas were enrolled between October 2011 and July 2014. All patients received at least one dose of study drug. Primary reasons for discontinuation included progressive disease (56%) and adverse events (25%). Grade 3 or over adverse events and any serious adverse events were reported in 88% and 73% of patients, respectively. The most frequently reported grade 3 or over treatment-emergent related adverse events were thrombocytopenia (80%), neutropenia (27%), and anemia (12%). Among the 87 patients evaluable for efficacy, overall response rate was 28% (complete response 5%), with highest responses observed in patients with follicular lymphoma (overall response rate 56%), T-cell lymphoma (overall response rate 40%), and diffuse large B-cell lymphoma (overall response rate 31%). Further investigation of the safety and efficacy of abexinostat in follicular lymphoma, T-cell lymphoma, and diffuse large B-cell lymphoma implementing a less dose-intense week-on-week-off schedule is warranted. (Trial registered at: EudraCT-2009-013691-47)